Optimisation of Cover Thickness in Tyre Fibre Concrete under Elevated Temperature - Ibrahim, O. A.; Afodun, M. M.; Mije, F. G.; Ako, T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Failure of structural elements after fire outbreak is mostly attributed to spalling action. Spalling of concrete is an occurrence which results to decrease in the cross sectional area of the concrete elements, thus decreases the resistances to fire loads. This study, optimized the concrete cover thickness in tyre fibre concrete (TFC), which was subjected to single temperature load according to ISO 834 using graphical method. Three (3) samples were prepared from each series of mix containing tyre fibers of 10 mm width and varying length viz; 0%, 2.5%, 5.0% and 7.5%, using water cement ratio of 0.55. The samples were produced in 100 x 100 x 100mm cubes and tested for compressive strength. However, the cubes were structural modeled using TEDDS 2.0.01 and STAADPro v8i to under temperature load to determine optimum cover thickness through the deflection mode. The cover thickness for tyre-fibre concrete reduced from 25mm to 17.5mm under the same condition with the conventional concrete mixture. This shows that inclusion of tyre-fibre in concrete increases the fire resistance and reduces the cover thickness. It is recommended that tyre-fibre concrete should be used in our daily construction work for more durability.